DETECTION OF THE ANTIBACTERIAL ACTIVITY OF AGNPS BIOSYNTHESIZED BY PSEUDOMONAS AERUGINOSA - & Muslim, Hussein (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Both bacterial isolates were obtained from Al-Elwiya Teaching Hospital for Children, Baghdad, Iraq. Clinical specimens were isolated from wounds and identified by Gram staining and by Vitek 2. Silver nanoparticles (AgNPs) were synthesized by Pseudomonas aeruginosa, and Characterized by UV-Vis spectroscopy (UV), Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction(XRD). Antibacterial activity toward S. aureus was detected for the Silver nanoparticles that created by bacteria, Also the synergistic effect that will be  detected  between the antibiotics and   nanoparticles(AgNPs). The highest effect was recorded in the case of the combination of  (Doxycycline antibiotic with AgNPs) by  a diameter of inhibition zone reached to 45.33 mm  ,followed by 41.16 mm  for  the  combination of (Clindamycin and  AgNPs ).Antagonistic effect also observed in the case of the combination of (Erythromycin with AgNPs)  by inhibition zone reached to 16 mm. Minimum inhibitory concentration(MIC) of the biosynthesized AgNP detection for S. aureus was carried out with the following concentrations (0.005, 0.010, 0.015, and 0.020 mg/mL), the MIC of the biosynthesized AgNPs was 0.020mg/mL. About the detection of kill time for the biosynthesized AgNPs, the result showed that AgNPs required 120 min with 0.020mg/mL to kill the pathogenic bacteria Staphylococcus aureus.